Exploring Contemporary Trends and Challenges in Company Management: A Case Study of the Philippines' Corporate Landscape - Annatalia Luningning (International Journal of Science and Society, 2023)
In an era characterized by rapid globalization and technological advancement, understanding the complex dynamics of contemporary company management is crucial for sustainable business success. This study delves into the intricacies of company management within the unique context of the Philippines' corporate landscape, examining both the emerging trends and persistent challenges that shape organizational strategies. Through a mixed-methods approach that combines qualitative interviews with key stakeholders and quantitative analysis of industry reports, this research uncovers the evolving paradigms of agile leadership, digital transformation, and strategic human resource management. These trends reflect the global shift towards adaptive decision-making, technology integration, and workforce development. Concurrently, the study highlights the enduring challenges posed by regulatory intricacies, economic uncertainties, and socio-cultural considerations, underscoring their impact on the local business environment. By contextualizing these findings within the broader global management discourse, this study contributes to the understanding of the interplay between theory and practice in a diverse and dynamic corporate landscape. The implications extend beyond the Philippines, resonating with companies navigating similar trends and challenges worldwide, while offering a roadmap for adaptive management strategies.